Factors Supporting the Job Satisfaction of the Middle Healthcare Management - The Role of Work Conditions, Managerial Competencies and Social Support - Jankelová, Nadežda, 1966-
Identifikácia determinantov pracovnej spokojnosti manažérov v podmienkach slovenského zdravotníctva.